Inference of FDI in Indian retail sector: Some Reflections - Deshpande, Mahesh; Gaddi, Alok; Patil, Shrinivas R (Journal of Entrepreneurship, Business and Economics; Vol 2 No 2 (2014), 2014)
Purpose- The Indian retail market, which was largely unorganized till the 1980s, has undergone an immense transformation in post-liberalization era. However, valued at $ 450 billion, the Indian retail sector is still relatively small by global standards, with giants like Wal-Mart alone reporting over US $ 315 billion (approx) in global sale. India is estimated to have around 15 million retail outlets, making it the country with the highest retail outlet density in the world. A.T. Kearney, a well known international management consultancy, in the year 2009, identified India as the most attractive retail destination in the world. With a significant contribution to the national GDP (10 percent) and employment (8 percent, second largest employer after agriculture) this sector can definitely be referred as one of the pillars of the Indian economy. Design/methodology/approach- The paper pulls together various strains of research and data gathere from sound databases to discuss the status. Findings- In their preparation to face fierce competitive pressure, Indian retailers must come to recognize the value of building their own stores as brands to reinforce their marketing Positioning, to communicate quality as well as value for money. Sustainable competitive advantage will be dependent on translating core values combining products, image and reputation into a coherent retail brand strategy. Viewpoint Reference to this paper should be made as follows: Deshpande, M., Gaddi, A., Patil, S. R. (2014). “Inference of FDI in Indian retail sector- Some Reflections”, Journal of Entrepreneurship, Business and Economics, Vol. 2, No. 2, pp. 82–97.